Family experiences in discovering Autism Spectrum Disorder: implications for family nursing - Tassia de Arruda Bonfim; Bianca Cristina Ciccone Giacon-Arruda; Catchia Hermes-Uliana; Sueli Aparecida Frari Galera; Maria Angélica Marcheti (Associação Brasileira de Enfermagem, 2020)
abstract Objectives: to describe the family's experience in the process of discovering the diagnosis and initiation of treatment of children with Autism Spectrum Disorder. Methods: this qualitative and descriptive study interviewed nine relatives of eight children on autism spectrum. They were inserted in health services, public education, and Association of Parents and Friends of The Exceptional of cities in the countryside of the Center-West. Data were collected through open interviews from July to September 2017. Data was submitted to thematic analysis. Results: at the beginning, the family was difficult to perceive the first atypical signs presented by the children. Families experience situations of vulnerability, since support networks are insufficient. The school played a significant role in recognizing unexpected behaviors. Final Considerations: support, offered by nurses, health professionals, school and social support devices, is important to family and children in this trajectory.